Program Kemitraan Masyarakat(PKM): Sirkumsisi Massal dengan Rumah Sunat - Sapada, Edy; Asmalinda, Wita; Wahyuni, Intan (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2024)
Circumcision is a minor surgical procedure with the main action of cutting (incising) some parts of the skin covering the male genitalia. The type of community service implemented is the Community Partnership Program (PKM), providing direct services to the community through mass circumcision activities. This community service activity was carried out for 2 days which were used for preparation in the form of processing community service permits, preparing places, facilities, and training tools, as well as consumption and lunch for participants and organizers of the circumcision activity. Of the 20 participants, all were circumcised well and smoothly. The evaluation was conducted check control to the Ibnu Sina Circumcision House for a check-up. It can be concluded that this mass circumcision activity is very useful and the less fortunate surrounding community feels its benefits.